Holistic Blended Values: Another Social Entrepreneurship Paradigm - Muhammad, Helmi (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
This study seeks to comprehend in-depth how social entrepreneurship (SE) practices from a business standpoint in Islamic boarding schools, as well as what values emerge in SE practices. The qualitative research design is descriptive exploratory, with a holistic single-case study conducted at the Sidogiri Islamic boarding school in Pasuruan, Indonesia. In-depth interviews, field observations, focused discussions, and a review of supporting documents were employed to collect data. In-depth interviews, field observations, focused discussions, and a review of supporting documents were used to collect data. Purposive sampling was used to select key informants, and the snowball sampling technique was used to select other informants based on key informant recommendations. After maintaining quality standards through data triangulation, observers and sources, and member checks, data analysis employs an interactive model. According to the findings, SE practices are implemented through a combination of corporate social responsibility programs, bottom-of-the-pyramid orientation, other SE activities, and spirituality. The distinction of SE development in the Islamic boarding school-based business perspective in Indonesia is this balance. The balance of the SE program, as reflected in the holistic blended value, is critical to the business's existence and sustainability. The last section goes over the implications and future research.